Apakah Pasar Modern Menurunkan Pendapatan Pedagang di Pasar Tradisional? (Analisis Binary Logistik) - Wulandari, Ni Luh Gede Ita; Meydianawathi, Luh Gede (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 2, Agustus 2016 (pp. 89 - 176), 2017)
The existence of the modern art market can be a dilemma for merchants who have capital to small scale and can potentially cause a decrease income traders in Sukawati Art Market. This study aimed to analyze the effect of sales volume, business location, and hours of operation simultaneously and partially on the income trader in Sukawati Art Market after the development of modern art market. Respondets of this reseach are 89 trader and owner of small scale business located at Sukawati Art Market. The data collected through interviews, questionnaires, and observations. The analysis technique used is Binary Logistic. Results of the research showed that the probability of revenues was declining to 71,9  percent and those who has fixed revenues was 29,1 percent of the responden. Variable sales volume, business location, and hours of operation simultaneously and partially significant effect on the income trader in Sukawati Art Market.
Keywords: pendapatan pedagang; volume penjualan; lokasi usaha; jam operasional